Social responsibility appeal and cross-lagged effects of perceived norms on mask-wearing behavior during the COVID-19 pandemic - Kim, Hye Kyung (2025)
This study extends the Theory of Normative Social Behavior by examining the cross-lagged effects of perceived norms on mask-wearing intention and behavior during an evolving COVID-19 pandemic. We also investigate the normative mechanisms of how social responsibility appeals improve compliance with mask-wearing behavior. A two-wave panel survey (N = 767) was conducted in Singapore in March and April 2020. Findings show that injunctive norms increase subsequent intention, whereas descriptive norms reduce subsequent behavior. Individuals may find it unnecessary to wear masks when they perceive many others are engaging in the action. Our result shows that this counterproductive effect could be mitigated by a greater sense of social pressure to comply, which can be reinforced by using social responsibility appeals. Our findings offer insights for theory extension and norms-based intervention strategies in pandemic contexts.